Persistent post-surgical pain and its relationship to health-related quality of life in Pakistani women after breast cancer surgery - Rukhsana Bibi; Khomapak Maneewat; Hathairat Sangchan; Wipa Sae-sia (Belitung Nursing Journal, 2022)
Background: Breast cancer is the most commonly diagnosed cancer in women; it is also the second-leading cause of death from cancer. Persistent pain after breast cancer surgery is a serious clinical problem that negatively impacts the health-related quality of life of breast cancer survivors. Although persistent post-surgical pain following breast cancer surgery has long been under-reported; however, it is less explored in Pakistan's geographical background. Objective: The study aimed to examine the persistent post-surgical pain after breast cancer surgery and its relationship to health-related quality of life among Pakistani women. Methods: A descriptive correlational research design was employed in this study. The Brief Pain Inventory Short Form (BPI-SF) was used to assess the persistent post-surgical pain. The Functional Assessment of Cancer Therapy-Breast (FACT-B) was used to measure the health-related quality of life. Data were collected between February and May 2019 from Pakistani women who have undergone breast cancer surgery for at least three months and attended follow-up visits at two tertiary care hospitals in Pakistan. A Spearman’s correlation coefficient was used for data analysis. Results: The study included 91 Pakistani women. The participants were all females, with an average age of 45.6 years (SD = 6.53). The majority received radical mastectomy (n = 84, 92.3%) with adjuvant therapy (n = 91, 100%). The prevalence of breast surgery-related persistent pain was 100%, with 63 (69.2%) rating the pain as moderate to severe and reported neuropathic pain. The data analysis revealed a statistically significant negative correlation between BPI-SF items and FACT-B dimensions (r = -.43, p < 0.01). The participants appeared to show the highest score of the FACT-B in the social/family well-being (M = 16.58, SD = 3.44). The lowest score of the FACT-B was physical well-being (M = 6.98, SD = 6.38). Conclusion: Persistent post-surgical pain has a negative impact on the health-related quality of life of Pakistani women breast cancer survivors, particularly on their physical well-being. Therefore, follow-up care of breast cancer survivors after treatment completion requires proper persistent pain-relief treatments and interventions to control pain and maintain health-related quality of life in oncology and research in this sphere. This basic knowledge from this study will enlighten the nurses and health care professionals to pay more attention to pain management and regular evaluation of persistent post-surgical pain after breast cancer surgery in order to improve their health-related quality of life.